Emerging Targets in Pituitary Adenomas: Role of the CXCL12/CXCR4-R7 System. (16th November 2014) - Barbieri, Federica; Thellung, Stefano; Würth, Roberto; Gatto, Federico; Corsaro, Alessandro; Villa, Valentina; Nizzari, Mario; Albertelli, Manuela; Ferone, Diego; Florio, Tullio
Abstract : Chemokines are chemotactic regulators of immune surveillance in physiological and pathological conditions such as inflammation, infection, and cancer. Several chemokines and cognate receptors are constitutively expressed in the central nervous system, not only in glial and endothelial cells but also in neurons, controlling neurogenesis, neurite outgrowth, and axonal guidance during development. In particular, the chemokine CXCL12 and its receptors, CXCR4 and CXCR7, form a functional network that controls plasticity in different brain areas, influencing neurotransmission, neuromodulation, and cell migration, and the dysregulation of this chemokinergic axis is involved in several neurodegenerative, neuroinflammatory, and malignant diseases. CXCR4 primarily mediates the transduction of proliferative signals, while CXCR7 seems to be mainly responsible for scavenging CXCL12. Importantly, the multiple intracellular signalling generated by CXCL12 interaction with its receptors influences hypothalamic modulation of neuroendocrine functions, although a direct modulation of pituitary functioning via autocrine/paracrine mechanisms was also reported. Both CXCL12 and CXCR4 are constitutively overexpressed in pituitary adenomas and their signalling induces cell survival and proliferation, as well as hormonal hypersecretion. In this review we focus on the physiological and pathological functions of immune-related cyto- and chemokines, mainly focusing on the CXCL12/CXCR4-7 axis, and their role in pituitary tumorigenesis. Accordingly, we discuss the potential targeting of CXCR4 as novel pharmacological approach for pituitary adenomas.